Sosialisasi dan Pendampingan Pembuatan Nomor Induk Berusaha untuk Pelaku UMKM di Kelurahan Tlogopatut - Pranata, Dandy Dimas; Ikaningtyas, Maharani (Jurnal Bisnis Indonesia, 2024)
Micro, Small and Medium Enterprises (MSMEs) play a vital role in economic growth and job creationin Indonesia. However, most MSME players often face obstacles in applying for business licences,including the Business Identification Number (NIBregulatory reform efforts. This study aims toinvestigate the impact of a socialisation and mentoring programme on NIB production for MSMEs inKelurahan Tlogopatut, Gresik. This research uses a qualitative approach with in-depth observationand field data collection methods. The results showed that an effective socialisation programme andcareful mentoring had a positive impact on MSME players. MSME players who participated in theprogramme gained a better understanding of the NIB requirements and application procedures. Inaddition, assistance in form filling and the licensing process also helped to reduce the time needed toobtain an NIB and avoid bureaucratic problems that could potentially harm businesses. This researchhas significant implications in the context of business ease and MSME development in KelurahanTlogopatut, Gresik. The results highlight the importance of local government and other stakeholders'efforts in providing effective socialisation and mentoring programmes to support MSME actors inmeeting licensing requirements, particularly NIB. This is a key step.Keywords: Socialisation; Mentoring; NIB; MSME; Business Actors